Evaluation of caregivers' knowledge, beliefs and practices regarding oral lesions in HIV-patients: A pilot study (AOSIS, 2013)
Seventy to ninety percent of HIV-infected individuals have oral lesions that affect their quality-of-life. Caregivers play an important role in complementing the healthcare team. It is essential that the caregivers have optimal knowledge, beliefs and practices toward the management of care regarding oral-lesions in HIV-infected patients in caregiving institutions in Johannesburg, South Africa. To measure the knowledge, beliefs and practices relating to oral lesions in HIV infection amongst caregivers in caregiving institutions in Johannesburg. This cross-sectional pilot study conducted during 2005 and 2006 involved caregivers in palliative care institutions in Region 8, Johannesburg Metropolitan area (n= 52). Using a questionnaire, information obtained included demographics, knowledge, beliefs and practices with regard to oral care for HIV-positive patients. Principal component analysis was used to extract questionnaire items of the knowledge domain. The knowledge domain displayed excellent internal consistency (Cronbach α-score of > 0.91). Of the caregivers, 65.4%had received training in oral care. Compared to caregivers not trained in oral care (NTOC), those caregivers trained in oral care (TOC) were more likely to be older (31 yrs vs. 44 yrs; p = 0.001), female (72%vs. 94%; p = 0.03) and were less likely to be employed on a full-time basis (94%vs. 68%; p = 0.03). Compared with NTOCs, TOCs had more knowledge regarding HIV-specific lesions and 'routine' oral-care for the patients (p < 0.005). Similarly, TOCcaregivers had more positive beliefs about oral care for those living with HIV (p < 0.05). Offering training in oral healthcare to caregivers improves their knowledge of oral lesions and their beliefs about oral care.